The relationship between the BMI value of children and the financial situation of families, as well as the age of children - Wioletta Waksmańska; Bousława Kupczak-Wiśniowska (Kazimierz Wielki University, 2024)
Aim: The research aimed to establish whether the family's financial situation had an impact on the BMI values of the children studied, to determine the link between the family's financial situation, the child's age and the frequency children were given selected foodstuffs, as well as to verify whether the frequency of consumption of selected foodstuffs has an impact on children's BMI values. Methods: BMI values were calculated for each child. Dietary habits were studied using a developed proprietary questionnaire. The questionnaire contained a list of products from 12 food groups, wherein vegetables and fruit were analysed separately, but without a division into those rich in vitamin C and carotene. Results: Analysis of the study group according to financial situation showed, to name a few, that the median consumption of fish, cold meats and potatoes among children from families declaring their financial situation as average was lower than that in the remaining groups. Children with a good financial situation consumed eggs and poultry statistically significantly more often than those with an average financial situation, and significantly less often - cakes and biscuits. Children over 11 years old consumed ready sauces (ketchup, mayonnaise) more often than younger children. Conclusion: The consumption of particular foodstuffs was affected by the families' financial situation and the age of children. Children from families with an average financial situation consumed vegetables less often than the remaining children. Despite there being no effect of the frequency of particular foodstuffs consumption on BMI, one in five people were overweight. It is crucial that the healthy lifestyles and proper diet programmes are implemented in educational establishments.